Effect of long-term administration of arsenic (III) and bromine with and without selenium and iodine supplementation on the element level in the thyroid of rat - Kotyzová, Dana; Eybl, Vladislav; Mihaljevic, Martin; Glattre, Eystein (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2005)
The aim of this study was to evaluate the influence of arsenic and bromine exposure with or without iodine and selenium supplementation on the element level in the thyroid of rats. Four major groups of Wistar female rats were fed with respective diets: group A - standard diet, group B - iodine rich diet (10 mg I/kg food), group C - selenium rich diet (1 mg Se/kg) and group D - iodine and selenium rich diet (as in group B and C). Each group was divided into four subgroups per 7 animals each receiving either NaAsO(2) ip (6.5 mg.kg(-1) twice a week for two weeks and 3.25 mg.kg(-1) for six weeks) or KBr in drinking water (58.8 mg.l(-1)) for 8 weeks or combined administration of both substances. Remaining subgroup served as controls. After 8 weeks thyroid glands were analyzed by ICP-MS for As, Br, Se, and I content. The exposition of rat to arsenic or bromine causes the accumulation of these elements in the thyroid gland ( approximately 18 ppm of As, approximately 90 ppm of Br) and significantly affects iodine and selenium concentration in the thyroid. In iodine and/or selenium supplemented rats the bromine intake into the thyroid was lowered to approximately 50% of the level in unsupplemented animals. Also selenium thyroid level elevated due to KBr administration was lowered by iodine supplementation in the diet. The accumulation of arsenic in the thyroid was not influenced by selenium or iodine supplementation; however, As(III) administration increased iodine thyroid level and suppressed selenium thyroid level in selenium or iodine supplemented group of animals.
Keywords: potkani Wistar; jod; Rats; Female; selen; Thyroid Gland; Arsenic; Animals; Bromine; ženské pohlaví; krysa rodu Rattus; Rats, Wistar; brom; Iodine; zvířata; arsen; štítná žláza; Selenium